The Relationship Between The Use Of Islamic Youtube Channels And The Understanding Of Religious Material Among Islamic Religious Education Students At Zainul Hasan Islamic University In Genggong, Probolinggo - Dinoval Aziz, Kevin; Khumaidi, Ahmad; Islam, Saiful (Qawwam : The Leader's Writing, 2026)
This study aims to analyze the relationship between the use of Islamic YouTube media and the understanding of religious material among Islamic Education (PAI) students at Zainul Hasan Genggong Islamic University in Probolinggo. The study used a quantitative correlational approach with a cross-sectional design. The study population consisted of 141 PAI students, with a sample of 65 students selected using simple random sampling based on the Slovin formula. Data were collected through a questionnaire measuring the intensity, consistency, content quality, and selectivity of Islamic YouTube usage, as well as a religious comprehension test covering the aspects of aqidah, fiqh, and akhlak. The validity of the instruments was confirmed through expert validation and factor analysis in SPSS (factor loadings > 0.5), while reliability yielded Cronbach s Alpha values of 0.80 (variable X) and 0.86 (variable Y). Descriptive statistics indicate that 75.4% of respondents fall into the moderate category regarding Islamic YouTube usage, with a mean usage score of 74.4 (SD = 9.66) and a mean religious understanding score of 76.0 (SD = 10.64). Pearson s correlation analysis yielded r = 0.804 (p < 0.01), indicating a very strong positive relationship between the use of Islamic YouTube and students understanding of religious material. These findings highlight the need for the systematic integration of digital media into the Islamic Education curriculum to enhance students religious literacy and understanding.